Binge drinking in adolescents and college students - Marczinski, Cecile A. (Nova Science Publ., 2009)
Introduction -- Differentiating binge drinking from social drinking and chronic drinking/alcoholism -- Binge drinking demographics -- Definition of a binge -- Social and environmental factors and binge drinking -- Neurocognitive and health effects of binge drinking in adolescents and college students -- Animal models of adolescent and adult binge alcohol use -- Binge drinking, impaired driving and other health risk behaviors -- Binge drinking and emergency department visits -- Screening and brief interventions in the emergency department -- Behavioral control models and alcohol : why loss of control over drinking might stem from neurocognitive changes when drinking -- Binge drinkers and their particular vulnerability to the acute effects of alcohol -- Binge drinking and alcohol tolerance -- Before the first drink : at risk individuals for the binge consumption of alcohol -- Alcohol expectancies and binge alcohol use -- Trendy cocktails : mixing energy drinks and alcohol -- Prevention and intervention strategies -- Binge drinking in young people : where do we go from here?